Stigma towards eating disorders : differences in age, gender, and education in an Icelandic sample - Steinunn Þórarinsdóttir 1992- (2022)
Eating disorders are a form of mental illness, and studies have indicated stigma towards those who experience eating disorders in society. Stigma towards eating disorders has not been studied in Iceland, and it is unknown what personal factors contribute to stigma. The three questions the current study sought to answer were: 1) does stigma towards those with eating disorders differ by age; 2) does stigma towards those with eating disorders differ by gender; and 3) does stigma towards those with eating disorders differ according to educational level. The “Eating Disorder Stigma Scale” questionnaire was utilized and split into four subscales. There were 222 participants who were recruited by convenience sampling. 33 participants were male, and 185 participants were women. The age range spanned from 19 years old to 84 years old. The current study showed a significant positive relationship between age and stigma towards individuals with eating disorders, with increased stigma amongst older participants. Additionally, the results showed that men had higher levels of stigma towards individuals with eating disorders than women, with a significant difference in the overall score and all four subscales. The results also showed that level of education only had a significant effect on one of the subscales, that is, the subscale that measured trivialization. In conclusion the current study showed that stigma towards eating disorders is present in an Icelandic sample. Keywords: Eating disorders, stigma, age differences, gender differences, educational differences. Átraskanir eru tegund af geðrænum sjúkdómum og rannsóknir hafa bent til fordóma gagnvart þeim sem greinast með átraskanir í samfélaginu. Fordómar gagnvart átröskunum hafa ekki verið rannsakaðir í íslensku samfélagi og ekki er vitað hvaða persónulegir þættir stuðla að fordómum. Núverandi rannsókn leitaðist við að svara þremur spurningum: 1) eru fordómar gagnvart þeim sem eru með átröskunarsjúkdóma mismunandi eftir aldri; 2) eru fordómar gagnvart þeim sem eru með ...